Facilitating creative participation and collaboration in online spaces: the impact of social and technological factors in enabling sustainable engagement. Issue 2 (3rd April 2017) - Literat, Ioana
ABSTRACT: This article investigates the role of social and technological factors in enabling sustainable creative participation in online environments. To facilitate a deeper understanding of these dynamics, I describe and analyse the implementation of a creative participatory project across three online platforms: as a series of tasks on Mechanical Turk, as a public collaboration on hitRECord, and as a participatory online course on Peer 2 Peer University. In discussing the three implementations, particular attention is paid to the norms and hierarchies of participation on each platform, the motivations driving participants to engage in online creative projects, and the significance of technological features in supporting the aims and ethos of participation in each case. This comparative analysis allows for a better understanding of the factors that facilitate or, conversely, hinder participatory creativity online, contributing to contemporary discussions aiming to explicate the parameters of creative participation and collaboration in online projects.